Multi-Omics Analysis of the Therapeutic Value of MAL2 Based on Data Mining in Human Cancers - Yuan, Jing; Jiang, Xiaoyan; Lan, Hua; Zhang, Xiaoyu; Ding, Tianyi; Yang, Fan; Zeng, Da; Yong, Jiahui; Niu, Beibei; Xiao, Songshu (Frontiers in Cell and Developmental Biology, 2022)
Recent studies have reported that MAL2 is an important regulator in cancers. Here, we downloaded data from multiple databases to analyze MAL2 expression and function in pancancer, especially in OC. Gene Expression Profiling Interactive Analysis (GEPIA) databases was used to examine MAL2 expression in 13 types of cancer. Kaplan-Meier Plotter database was used to analyzed the overall survival rate of MAL2 in pancancer. COSMIC, cBioPortal and UCSC darabased was performed to examine MAL2 mutation in human cancers. Metascape, STRING and GeneMANIA websites were used to explore MAL2 function in ovarian cancer (OC). Furthermore, ggplot2 package and ROC package were performed to analyze hub genes expression and undertake ROC analysis. Drug sensitivity of MAL2 in OC was examined by the GSCALite database. In order to verify the results from databased above, Real-time quantitative polymerase chain reaction (qRT-PCR) and Western Blotting were conducted to detect the expression of MAL2 in OC cells. CRISPR/Cas9 system was used to knockout the MAL2 gene in the OC cell line HO8910 and OVCAR3, using specific guide RNA targeting the exons of MAL2. Then we performed proliferation, colony formation, migration, and invasion assays to investigate the impact of MAL2 in OC cell lines in vivo and in vitro. EMT associated biomarkers were significantly altered in vitro via Western blotting and qRT-PCR. Taken together, we observed that MAL2 was remarkably dysregulated in multiple cancers and was related to patient overall survival (OS), mutation and drug sensitivity. Furthermore, experimental results showed that MAL2 deletion negatively regulated the proliferation, migration, invasion and EMT of OC, indicating that MAL2 is a novel oncogene that can activate EMT and significantly promote both the proliferation and migration of OC in vitro and in vivo and provide new clues for treatment strategies.